Democratic Values in Education: A Theoretical Examination of Ukrainian Children and Youth in Polish Schools Post-February 2022 - Federowicz, Michał; Terepyshchyi, Serhii (Studia Warmińskie, 2023)
The massive influx of Ukrainian people into Poland after February 24, 2022, has posed unprecedented challenges and opportunities for educational institutions. This article aims to lay the theoretical foundation for understanding how democratic values can be integrated into the Polish educational system to foster mutual cultural understanding, civic engagement, and social inclusion. Key concepts such as Democratic vs. Anti-democratic Values, Citizenship, Involvement, Freedom and Education for Peace, and others are analyzed to offer a comprehensive perspective. The article also underscores the need for empirical studies to further validate and refine these theoretical frameworks, given the unique and evolving socio-cultural landscape of Polish schools today.